Asian Cultures and Contemporary Tourism (Perspectives on Asian Tourism,, 2018)
This book focuses on cultures that shape contemporary Asian tourist experiences. The book consists of 10 chapters, which are organised into two themes: Collectivist Culture and Wellbeing. The chapters cover emerging forms of tourism (e.g., wedding and bridal photography tourism, roots/affinity tourism and shamanic tourism), investigate a wide range of topics (e.g., tourist motivation, tourist anxiety and decision making) and consider Asian perspectives from diverse backgrounds (e.g., China, Hong Kong, Singapore, Taiwan, South Korea, Japan, Philippines, Malaysia, Indonesia, India, Bangladesh, and Nepal). The book provides tourism researchers, students and practitioners a consolidated, comprehensive and updated reference for the understanding of Asian tourists. "The book has fruitfully brought together different perspectives and advances current understanding of Asian tourists from the history to current trends, from motivations to constraints, from the influence of culture and religion on travel behaviour to the search of social freedom through travel, and from destination choice to destination avoidance. The most important contribution of this book is that it has built an intellectual platform for many Asian scholars to share their ideas and works with the international tourism academy". - Professor Kaye Chon, Editor-in-Chief, Asia Pacific Journal of Tourism Research; Dean, School of Hotel and Tourism Management, The Hong Kong Polytechnic University.